Myron Charles Taylor papers - Taylor, Myron Charles, 1874-1959.
Correspondence between Presidents Franklin D. Roosevelt and Harry S. Truman and Pope Pius XII; U.S. Dept. of State correspondence and memoranda; Taylor's memoranda of his meetings with the Pope, with other Vatican officials, and with diplomats accredited to the Vatican; and his correspondence with Protestant clergymen. Correspondents include the secretary of state of the Vatican, Luigi Maglione; assistant secretaries of state, Domenico Tardini and Giovanni Battista Montini (later Pope Paul VI); apostolic delegate to the United States, Amleto Giovanni Cigognani; papal nuncio to France, Angelo Giuseppe Roncallo (later Pope John XXIII); Methodist Episcopal Church bishop, G. Bromley Oxnam; and bishop of the Evangelische Kirche in Berlin-Brandenburg, Otto Dibelius.
Typewritten transcripts.
Industrialist, diplomat, and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Cicognani, Amleto Giovanni, -- 1883-1973 -- Correspondence; Dibelius, Otto, -- 1880-1967 -- Correspondence; John -- XXIII, -- Pope, -- 1881-1963 -- Correspondence; Maglione, Luigi, -- 1877-1944 -- Correspondence; Oxnam, G. Bromley -- 1891-1963 -- Correspondence; Paul -- VI, -- Pope, -- 1897-1978 -- Correspondence; Pius -- XII, -- Pope, -- 1876-1958.; Pius -- XII, -- Pope, -- 1876-1958 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Tardini, Domenico, -- 1888-1961 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; United States. -- Department of State; Catholic Church -- Foreign relations -- United States; Diplomatic and consular service, American -- Vatican City; Protestant churches -- Clergy -- Correspondence; United States -- Foreign relations -- 20th century; Vatican City -- History; Diplomats; Industrialists; Lawyers